DETERMINATION OF THE STELLAR SCINTILLATION PROPERTIES WITH THE FAST-PHOTOMETRIC CAMERA - Shakhrukhanov, O. S. (Одеські астрономічні публікації, 2013)
In the present study it is shown that a television camera with adjustable signal storage time enables to measure the frequency and amplitude of the stellar scintillation.